2019
DOI: 10.1002/jnr.24386
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen distribution in mouse hippocampus

Abstract: The hippocampus is a limbic structure involved in the consolidation of episodic memory. In the recent decade, glycogenolysis in the rodent hippocampus has been shown critical for synaptic plasticity and memory formation. Astrocytes are the primary cells that store glycogen which is subject to degradation in hypoglycemic conditions. Focused microwave application to the brain halts metabolic activities, and therefore preserves brain glycogen. Immunohistochemistry against glycogen on focused microwave‐assisted br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 98 publications
1
17
0
Order By: Relevance
“…Glycogen in astrocytes is an emerging factor in memory consolidation. While astrocytes are the cell type that stores appreciable amounts of glycogen, their glycogen storage is heterogeneous in that there are glycogen-rich astrocytes and glycogen-poor astrocytes distinguished by the presence of glycogen largeparticles 50,51 In the current study, we showed the composition of adrenoreceptor subtypes is likely heterogeneous in individual astrocytes. Since astrocytic cAMP promotes glycogen metabolism, this may underlie the heterogeneous glycogen distribution.…”
Section: Discussionmentioning
confidence: 53%
“…Glycogen in astrocytes is an emerging factor in memory consolidation. While astrocytes are the cell type that stores appreciable amounts of glycogen, their glycogen storage is heterogeneous in that there are glycogen-rich astrocytes and glycogen-poor astrocytes distinguished by the presence of glycogen largeparticles 50,51 In the current study, we showed the composition of adrenoreceptor subtypes is likely heterogeneous in individual astrocytes. Since astrocytic cAMP promotes glycogen metabolism, this may underlie the heterogeneous glycogen distribution.…”
Section: Discussionmentioning
confidence: 53%
“…Glycogen storage in the adult brain is highly compartmentalized, with the highest levels in the hippocampus, striatum, and superficial layers of the cortex (Oe et al, 2016). Immunohistochemical studies showed that glycogen has a punctate distribution localized predominantly in astrocytic processes (Oe et al, 2016;Hirase et al, 2019). These studies further indicated an astrocytic heterogeneity, whereas some astrocytes were ''glycogen-rich'' while others found to be glycogen-poor.…”
Section: Energy Metabolism During Neurodegenerationmentioning
confidence: 96%
“…For decades astrocytes have been considered fundamental for brain functions because of their metabolic support to neurons and for their ability to regulate the extracellular levels of ions, neurotransmitters, and metabolites, thus maintaining the best conditions for neuronal firing. For example, the brain contains a small amount of glycogen, and this glycogen is found mainly in astrocytes, and is particularly enriched in the hippocampus [50]. This observation is relevant when we consider the role of hippocampus in memory processes [51][52][53].…”
Section: The Role Of Glial Cells In Memorymentioning
confidence: 96%